Development and structural basis of a two-MAb cocktail for treating SARS-CoV-2 infections - Chao Zhang (Nature Portfolio, 2021)
Here, the authors identify and characterize two mouse-derived monoclonal antibodies against SARS-CoV-2 spike protein that target different epitopes in RBD and block the interaction S/ACE2 and show that a formulated humanized version cocktail exhibits prophylaxis and therapeutic antiviral effects in an hACE2-adenovector expressed mouse model.